Trace metal fluxes in bulk deposition, throughfall and stemflow at two evergreen oak stands in NE Spain subject to different exposure to the industrial environment - Avila, Anna; Rodrigo, Anselm (Atmospheric Environment, 2004)
We compare here the bulkdeposition, throughfall and stemﬂow ﬂuxes of dissolved trace metals in two holm oak (Quercus ilex L.) forests in the Montseny Mountains (NE Spain) with the aim of: (1) applying different methods to distinguish between dry deposition and canopy leaching and (2) to add to the almost non-existing deposition measurements for dissolved Cu, Pb, Mn, V, Zn, Ni and Cd in two Spanish forests differentially exposed to the urban and industrial environment. No signiﬁcant differences in mean bulkdeposition concentrations or ﬂuxes were found between sites, indicating little differential effect of the urban/industrial environment on bulkprecipitation chemistry. At both sites, throughfall and stemﬂow ﬂuxes increased relative to bulkdeposition for all elements, except for Zn and Cd. The relative contribution of leaching and dry deposition was evaluated through: (1) the seasonal variability of throughfall, (2) regressions of element ﬂuxes on water ﬂux in net throughfall, (3) washing branches and metacrylate plates, and (4) the sequential washing of branches. Results indicated that leaching was the main enrichment process for Mn. For Ni, except the sequential washings, all other evidences also pointed to leaching. For Cu, Pb, Zn, Cd and V there was ample evidence for dry deposition. The fact that Zn and Cd had negative net throughfall ﬂuxes indicated that canopy uptake was greater than deposition (wet plus dry). Net throughfall ﬂuxes pointed to higher dry deposition onto the canopies in the more exposed site, but the occurrence of uptake impeached quantiﬁcation. Therefore, dry deposition was estimated from the recovered quantities from experimental washings of foliage, taken to represent the impaction of small particles onto the canopy. The foliage-wash ﬂuxes were, for Zn, Cu and Pb, respectively, 407, 25 and 16 g ha 1 yr 1 at the sheltered site and 423, 38 and 26 g ha 1 yr 1 at the exposed site. Deposition in bulkprecipitation (wet deposition+an unknown fraction of dry deposition mostly accounted by coarse particles settling gravitationally) was lower: 222, 6.3 and 6.5 g ha 1 yr 1 for Zn, Cu and Pb, respectively, averaged for the two sites
Keywords: Dry deposition; Leaching; Mediterranean forests; surrogate surfaces; throughfall; Trace metals

Trace metal fluxes in bulk deposition, throughfall and stemflow at two evergreen oak stands in NE Spain subject to different exposure to the industrial environment - Avila, Anna; Rodrigo, Anselm (Atmospheric Environment, 2004)
We compare here the bulkdeposition, throughfall and stemﬂow ﬂuxes of dissolved trace metals in two holm oak (Quercus ilex L.) forests in the Montseny Mountains (NE Spain) with the aim of: (1) applying different methods to distinguish between dry deposition and canopy leaching and (2) to add to the almost non-existing deposition measurements for dissolved Cu, Pb, Mn, V, Zn, Ni and Cd in two Spanish forests differentially exposed to the urban and industrial environment. No signiﬁcant differences in mean bulkdeposition concentrations or ﬂuxes were found between sites, indicating little differential effect of the urban/industrial environment on bulkprecipitation chemistry. At both sites, throughfall and stemﬂow ﬂuxes increased relative to bulkdeposition for all elements, except for Zn and Cd. The relative contribution of leaching and dry deposition was evaluated through: (1) the seasonal variability of throughfall, (2) regressions of element ﬂuxes on water ﬂux in net throughfall, (3) washing branches and metacrylate plates, and (4) the sequential washing of branches. Results indicated that leaching was the main enrichment process for Mn. For Ni, except the sequential washings, all other evidences also pointed to leaching. For Cu, Pb, Zn, Cd and V there was ample evidence for dry deposition. The fact that Zn and Cd had negative net throughfall ﬂuxes indicated that canopy uptake was greater than deposition (wet plus dry). Net throughfall ﬂuxes pointed to higher dry deposition onto the canopies in the more exposed site, but the occurrence of uptake impeached quantiﬁcation. Therefore, dry deposition was estimated from the recovered quantities from experimental washings of foliage, taken to represent the impaction of small particles onto the canopy. The foliage-wash ﬂuxes were, for Zn, Cu and Pb, respectively, 407, 25 and 16 g ha 1 yr 1 at the sheltered site and 423, 38 and 26 g ha 1 yr 1 at the exposed site. Deposition in bulkprecipitation (wet deposition+an unknown fraction of dry deposition mostly accounted by coarse particles settling gravitationally) was lower: 222, 6.3 and 6.5 g ha 1 yr 1 for Zn, Cu and Pb, respectively, averaged for the two sites
Keywords: Dry deposition; Leaching; Mediterranean forests; surrogate surfaces; throughfall; Trace metals

The chemistry of precipitation, throughfall and stemflow in two holm oak (Quercus ilex L.) forests under a contrasted pollution environment in NE Spain. - Rodrigo, a; Avila, a; Rodà, F (The Science of the total environment, 2003)
Atmospheric deposition was studied through measurements of bulk deposition, throughfall and stemflow at two sites of contrasted exposure to pollution in the Montseny mountains (Northeastern Spain). To explore the contribution of local or distant sources at both sites, concentration data and precipitation amounts (log transformed) for both bulk deposition and net throughfall were fitted by linear regression. These models indicated the more important contribution of washout scavenging processes and dry deposition at the pollution exposed site. This is relevant in the context of Mediterranean holm oak forests: up to now, most of the studies have been conducted in protected remote sites and were little representative of the fluxes in forests close to industrial activity, traffic, agriculture and residential areas.
Keywords: bulk deposition; Dry deposition; Holm oak forest; Leaching; N uptake; throughfall

The chemistry of precipitation, throughfall and stemflow in two holm oak (Quercus ilex L.) forests under a contrasted pollution environment in NE Spain. - Rodrigo, a; Avila, A.; Roda, F. (The Science of the total environment, 2003)
Atmospheric deposition was studied through measurements of bulk deposition, throughfall and stemflow at two sites of contrasted exposure to pollution in the Montseny mountains (Northeastern Spain). To explore the contribution of local or distant sources at both sites, concentration data and precipitation amounts (log transformed) for both bulk deposition and net throughfall were fitted by linear regression. These models indicated the more important contribution of washout scavenging processes and dry deposition at the pollution exposed site. This is relevant in the context of Mediterranean holm oak forests: up to now, most of the studies have been conducted in protected remote sites and were little representative of the fluxes in forests close to industrial activity, traffic, agriculture and residential areas.
The following values have no corresponding Zotero field: accession-num: 12670768
Keywords: bulk deposition; Dry deposition; Holm oak forest; Leaching; N uptake; throughfall

Influence of leaf litter type on the chemical evolution of a soil parent material (sandstone) - Madeira, M; Ribeiro, C (Biogeochemistry, 1995)
The influence of leaves of Quercus suber L. and Eucalyptus globulus Labill. and needles of Pinuspinaster Ait. on a sandstone substrate was assessed through lysimetric studies during a ten-year period at a site in Central Portugal. The decomposition rate of Q. suber leaf litter was similar to that of E. globulus and higher than that of P pinaster needle litter. The proportion of nitrogen released from the Q. suber leaf litter was higher than that lost from the other organic species. Such a release was proportional to the initial nitrogen content in the substrates. The concentrations of both NHa-N and NO3-N were much higher in leachates collected under Q. suber leaf litter than in those collected under the other organic substrates. A similar trend was found in the leachates collected under the mineral substrate influenced by the studied organic substrates. The leachate concentrations of mineral N (especially NOs-N) were higher from the mineral substrate under Q. suber leaf litter than from this organic substrate itself. The mineral substrate under leaf litter of E. globulus or needle litter of P pinaster showed an increase in exchangeable base cations and pH values, and a decrease in extractable Al. Conversely, in the substrate with Q. suber leaf litter there was only a slight increase in exchangeable base cations and pH values, and a decrease in extractable Al. These results combined with those obtained in soils underE. globulus plantations indicate that changes found in these soils are due to soil and forest m
Keywords: decomposition rate; elemental fluxes; EUCALYPTUS; Leaching; leaf litter; Pinus pinaster; Quercus suber; soil chemistry